The effects of growth medium on Flavobacterium columnare colony morphology and its phage resistance mechanisms - Smith, Katie (2019)
The freshwater bacterium Flavobacterium columnare is known to exhibit different morphologies when cultured in different media with bacteriophage. This could influence the type of phage-resistance mechanisms the bacteria use, such as CRISPR-Cas system or alterations which reduce bacteriophage adsorption. In this study the different morphologies which arise in different media when treated with bacteriophage was investigated to identify their favoured phage-resistance mechanism. The bacteria were screened for acquisition of new CRISPR spaces and tested for changes in phage adsorption. Results show that the growth medium itself influences the bacterial colony morphology, likely due to the difference in nutrients available. When exposed to bacteriophage, a small proportion of bacteria in HTC medium acquired new CRISPR spacers, however, the preferred phage-resistance mechanism appears to be something other than CRISPR-Cas overall, in SHIEH and HTC. Improved understanding of bacterial resistance mechanisms is useful towards the development of bacteriophage therapies.